Token governance in initial coin offerings: Implications of token retention and resale restrictions for ICO success - Johannes Fuchs; Paul P. Momtaz (Small Business Economics, 2024)
The high degree of asymmetric information in initial coin offerings (ICOs) increases the probability of moral hazard, adverse selection, and outright fraud. Token governance mechanisms may help mitigate such investment risks. Using novel data on token retention in the primary market and resale restrictions in the secondary market, we estimate the impact of these governance mechanisms on the fundraising success and post-funding performance of ICOs. First, we estimate the valuation elasticity of token retention, indicating that 10% fewer tokens sold increases the ICO funding amount by 3.2%. Second, restricting ICO investors' ability to resell tokens in the secondary market has a detrimental impact on the 12-month buy-and-hold abnormal return. We also discuss contingency effects of the specific implementations of these governance signals and show that the effects are moderated by the quality of the venture's human capital.
Keywords: G23; G24; L26; 330; Initial coin offering (ICO); Digital assets; Token allocation; Token issuance and resale restriction; Venture valuation and performance